Some important ethnohepatoprotective flora of Katarniaghat wildlife sanctuary - Singh, Rahul Kumar (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> This paper deals with ethnohepatoprotective studies on tribal community of Katarniaghat Wildlife Sanctuary., who use more than 25 medicinal Flora belonging to 19 families in various ailments related to liver problems as a hepatoprotective medicine in own traditional phytotherapy <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->